ODR Systems to Settle Divorces: How Clinical Legal Education Can Play a Role Using Online Technologies - Christopher Gibson (Washington University Journal of Law and Policy, 2026)
The access-to-justice gap in family law continues to widen, leaving thousands of self-represented parties struggling with forms, procedures, and courts that were not designed for them. Legal technology, particularly online dispute resolution (ODR) tools, offers an opportunity to simplify, guide, and democratize family matters, such as uncontested divorces moving through the family law courts. This Article explores how clinical legal education can contribute to—and benefit from—the design and implementation of such systems. Focusing on the AAA-Suffolk University Law School’s ODR Innovation Clinic, the Article analyzes the development of a platform for Massachusetts 1A uncontested divorces, which law students created in collaboration with the American Arbitration Association (and its online branch ODR.com), courts and community stakeholders. Drawing on experiential learning theory, user-centered design principles, and the legal and procedural landscape of family law, this Article proposes a model for legal education that not only prepares future lawyers for a changing profession, but also delivers meaningful access to justice. The Article concludes by identifying lessons for replication and future research at the intersection of ODR, pedagogy, and policy.
Keywords: #ODRDesign; #SelfRepresentedLitigants; #FamilyLawTech; #LegalEducationReform; #ClinicalLegalEducation